Valorization of Cordia gum: A Natural Hydrocolloid for Functional Food Innovation - Singh Ashmita; Singh Brahma N.; Thakur Monika (BIO Web of Conferences)
Gums, as natural hydrocolloids, play a crucial role in enhancing the functionality and stability of food products. The present study focuses on the extraction, characterization, and functional evaluation of Cordia fruit gum for its application in value-added food formulations. Traditionally used in the pharmaceutical industry, Cordia gum remains underutilized in the food sector. This research aims to optimize the extraction process, ensuring maximum yield while preserving functional properties. The physicochemical characterization, including rheological behaviour, moisture content, solubility, and particle size distribution, was conducted to establish its potential as a functional ingredient. Functional property assessments, such as emulsifying, stabilizing, water-holding, and foaming capacities, were performed to explore its suitability in food formulations. Cordia gum was successfully incorporated into innovative food products, including ginger-garlic paste, flavoured drinks, and nutritional formulations for lactating mothers. The findings highlight Cordia gum as a natural alternative to synthetic stabilizers and emulsifiers, supporting clean-label and sustainable food innovations. The study contributes to bridging the research gap by demonstrating the commercial viability of Cordia gum in functional food applications, paving the way for further exploration in food product development